2021
DOI: 10.1039/d1ta00421b
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up assembly of bimetallic nanocluster catalysts from oxide-supported single-atom precursors

Abstract: The precise synthesis and stabilization of oxide-supported bimetallic nanoclusters in the low-to-sub nanometer size regime is highly relevant in various fields, from optics and sensing to electrochemistry and catalysis. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…In fact, SACs are especially suitable to be studied by bulk averaging techniques such as XAS. Beyond the ex situ characterization, more important is to understand the dynamic behavior of SACs with XAS under operating conditions, as pointed out by various research groups. As X-rays can penetrate easily through solid materials in either crystalline or amorphous phase, XAS can account for reversible or irreversible transformation in catalysts sintering/agglomeration from atom to nanoparticle under oxidizing or reducing atmosphere as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, SACs are especially suitable to be studied by bulk averaging techniques such as XAS. Beyond the ex situ characterization, more important is to understand the dynamic behavior of SACs with XAS under operating conditions, as pointed out by various research groups. As X-rays can penetrate easily through solid materials in either crystalline or amorphous phase, XAS can account for reversible or irreversible transformation in catalysts sintering/agglomeration from atom to nanoparticle under oxidizing or reducing atmosphere as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite these high energy requirements, this process has attracted significant attention because it converts both methane and carbon dioxide, two major greenhouse gases, into the valuable chemical feedstocks, CO and H 2 . 6−8 One significant deactivation mechanism for DRM catalysts is the sintering of the active metal sites, a high-temperature process by which the catalytically active metal atoms migrate (Ostwald ripening) 9,10 and/or metal particles coalesce and form less and/or fewer active sites for the reaction (sintering). 11,12 Our research groups have previously reported that the initial deactivation of Ni/Al 2 O 3 catalysts under DRM conditions is caused by the sintering of the Ni particles with an apparent activation energy of 161 kJ mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Many heterogeneous catalysts suffer from deactivation over time due to coking and sintering during the catalytic reaction. Harsh operating reaction conditions, for example, high temperatures or high chemical potentials, are likely to cause severe deactivation because such conditions can increase the rates of coke formation, agglomeration of active metal sites, and/or other deactivating processes. Dry reforming of methane (DRM), in which methane is used to reduce CO 2 , is a classic example of an endothermic (Δ H 298K = + 247 kJ mol –1 ) catalytic reaction requiring harsh conditions (operating temperature > 600–700 °C), resulting in severe catalyst deactivation. , Despite these high energy requirements, this process has attracted significant attention because it converts both methane and carbon dioxide, two major greenhouse gases, into the valuable chemical feedstocks, CO and H 2 . One significant deactivation mechanism for DRM catalysts is the sintering of the active metal sites, a high-temperature process by which the catalytically active metal atoms migrate (Ostwald ripening) , and/or metal particles coalesce and form less and/or fewer active sites for the reaction (sintering). , Our research groups have previously reported that the initial deactivation of Ni/Al 2 O 3 catalysts under DRM conditions is caused by the sintering of the Ni particles with an apparent activation energy of 161 kJ mol –1 …”
Section: Introductionmentioning
confidence: 99%
“…The atomically dispersed nature of SACs allows the utilization of almost 100% of its activity, which bodes well for newer opportunities in several applications. Apart from carbon as a support material, several other porous metal oxides including 2D nanomaterials have been successfully utilized for the preparation of SACs. , …”
Section: Synthesis Of Fe-sacsmentioning
confidence: 99%